(untitled) (Research, Society and Development, 2019)
The present article proposes to present through a bibliographical research a brief discussion about the importance of the study of gender as an object of research in social representations, as a social construction generally used to reinforce the power relations existing in our environment. The theoretical approach is based on the studies developed in the area of Gender and brings as a thread the theory developed by Moscovici (1978), which allows us to analyze how social groups understand phenomena of reality.